Ergonomic Analysis of Noise Level and Mechanical Vibration on Rice Grinding Machine in Sangia Village, Sape Districts, Bima Regency - Isnaini Isnaini; Nazaruddin Nazaruddin; Budy Wiryono (Protech Biosystems Journal, 2022)
Rice milling equipment will really help farmers to process their produce continuously, but this tool has a weakness, namely mechanical vibrations and noise that arise when these tools operate. This study aims to determine the noise level of the rice milling machine and analyze the noise level of the rice milling machine. The method used in this research is an experimental method by conducting direct tests in the field. This study was designed using a Randomized Block Design (RAK). Parameters in this research include vibration value, noise level, work capacity, tool efficiency, and yield. Observational data were analyzed by analysis of variance at a significance level of 5%. If there is a treatment that has a significant effect, then it is further tested using the Honestly Significant Difference (BNJ) test at the same significant level. The results showed that the noise level of the rice milling machine at 600 Rpm (72.9 db) was lower than the rice milling machine in the first treatment, namely 1000 Rpm (74.5 db) and in the second treatment, 800 Rpm (73.5 db). db). The mechanical vibration of the rice milling machine at 600 Rpm (10.3 Hz) was lower than the rotation of the rice grinding machine at 1000 Rpm (12.5 Hz) and in the second treatment 800 Rpm (11.3 Hz).